Experiences, magic and coloniality. Students and witches considerations in Santiago del Estero, Argentina - Díaz Ledesma, Lucas Gabriel (2016)
This article aims at performing an analysis based on narratives about everyday experiences of subjects living in Santiago del Estero, Argentina, which are mediated by a mythical record: one of them religious and the other sex-generic. This time, we work on the relation between two characters: the student of magic and the witch, thus articulating mythical inscriptions with sex-generic imagery outlining the exercise of sexualities. Thereby, we try to understand how cultural patterns work, whose intelligibility occurs in dialogue with colonial processes of Santiago and the formation of crossbreeding. From communication and decolonial studies we seek to produce located and critical knowledge enabling us to politicize these issues and drive them out from their folklore status.